In Vitro and In Vivo Anti-AChE and Antioxidative Effects of Schisandra chinensis Extract: A Potential Candidate for Alzheimer's Disease. (20th February 2020) - Song, Xinmeng; Wang, Tiejie; Guo, Linxiu; Jin, Yibao; Wang, Jue; Yin, Guo; Jiang, Kun; Wang, Lijun; Huang, Hongrong; Zeng, Long
Abstract : Acetylcholinesterase (AChE) inhibition and antioxidants are two common strategies for the treatment in the early stage of Alzheimer's Disease (AD). In this study, extracts from nine traditional Chinese medical (TCM) herbs were tested for anti-AChE activity by Ellman's microplate assay and cytotoxicity by CCK-8. Based on its excellent AChE inhibition effect and its lowest cytotoxicity, Schisandra chinensis (SC) extract was selected to do the mechanism research. SC extract protected pheochromocytoma (PC12) cells against H2 O2 -induced toxicity by improving the cell survival rate in a dose-dependent manner. And it also showed significant free radical (DPPH) scavenging activities, ferric reducing antioxidant power (FRAP), and 2, 2′-Azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging. To confirm these results, the scopolamine-induced mice models were utilized in this study. Compared with the positive drug (piracetam), SC could also exhibit similar effects to alleviate the mice's cognitive deficits. Moreover, in the mice brain samples, the AChE activity and malondialdehyde (MDA) levels of SC-treatment group both showed a reverse as compared to model group. Taken together, these results all suggested that SC extract may be a potential therapeutic candidate for AD.